2019
DOI: 10.3390/jcm8060777
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Titanium Implant Thread Designs on Bone Healing: A Biomechanical and Histometric Study with an Animal Model

Abstract: Threads of dental implants with healing chamber configurations have become a target to improve osseointegration. This biomechanical and histometric study aimed to evaluate the influence of implant healing chamber configurations on the torque removal value (RTv), percentage of bone-to-implant contact (BIC%), bone fraction occupancy inside the thread area (BAFO%), and bone and osteocyte density (Ost) in the rabbit tibia after two months of healing. Titanium implants with three different thread configurations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Still, the healing chamber of group G3 presented a higher amount of BAFO%, indicating that the cellular reaction differed between the implant thread configurations. Other animal studies, where the healing chambers were examined in a longer time period (2 months), showed that healing chambers inserted in the cortical bone did not increase the BIC%, but increased implant biomechanical fixation at early times when compared to the conventional thread design [38]. This data sought in the literature helps to reinforce the initial hypothesis that the new implant design with the healing chambers elaborated in the implant threads more strongly in the initial stages of osseointegration of the implants.…”
Section: Discussionmentioning
confidence: 95%
“…Still, the healing chamber of group G3 presented a higher amount of BAFO%, indicating that the cellular reaction differed between the implant thread configurations. Other animal studies, where the healing chambers were examined in a longer time period (2 months), showed that healing chambers inserted in the cortical bone did not increase the BIC%, but increased implant biomechanical fixation at early times when compared to the conventional thread design [38]. This data sought in the literature helps to reinforce the initial hypothesis that the new implant design with the healing chambers elaborated in the implant threads more strongly in the initial stages of osseointegration of the implants.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding the macro-design, a cylindrical shape could lead to a higher bone-to-implant contact percentage, if compared with a conical geometry, providing that local factors such as depth of positioning, bone density, and surgical technique are equal [16,18,28]. Micro-geometry, threads pitch, and surface roughness could also significantly influence the primary stability [5,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the present study had the aim of evaluated both implant models (regular and new implant mcrogeometry) with the same surface treatment, to verify the importance of this factor (the macrogeometry) in the early time period of osseointegration. Primary stability is a prerequisite for achieving osseointegration of implants [1,12,13,21,25,26]. This results from the mechanical union between the bone and the implant that minimizes micromovements between the two structures and prevents the formation of fibrous tissue at its interface.…”
Section: Plos Onementioning
confidence: 99%
“…In this sense, alterations in the micro-and macrogeometry of the implant design are presented [6][7][8]. New surface treatments (micro topography), changing the physical and/or chemical characteristics [6,9,10], and new macrogeometries changing the implant design [11][12][13], are created by the researchers and, posteriorly, manufactured by the industry. These changes have resulted in better biological performance, as demonstrated in previous preclinical studies [14][15][16].…”
Section: Introductionmentioning
confidence: 99%